Molecular Docking and Molecular Dynamics Studies of Glu-Glu-Arg, Glu-Pro-Arg, and Pro-Arg-Pro Tripeptides to Reveal Their Anticancer and Antiviral Potentials - Yılmaz, Gözde; Çelik, Sefa; Özel, Ayşen Erbölükbaş; AKYÜZ, SEVİM (Wiley - VCH Verlag GmbH, 2024)
Bioactive peptides have been emerging as drug candidates with increasing importance in the last few decades. In this study, to evaluate the anticancer and antiviral properties of EER (Glu-Glu-Arg), EPR (Glu-Pro-Arg), and PRP (Pro-Arg-Pro) tripeptides, firstly their conformation preferences were searched, and the most stable optimized structure of each tripeptide was determined, using the molecular mechanics force field (MMFF) method and the Spartan06 program. Afterwards, each tripeptide was docked to SARS-CoV-2 spike protein receptor-binding domain (6M0J), SARS-CoV-2 main protease (6M03, 6LU7), spike glycoprotein (6VXX), DNA (1BNA), integrins (4WK0, 3ZDX, 1JV2) and epidermal growth factor receptor tyrosine kinase (4HJO). Moreover, molecular dynamics (MD) simulations were performed to validate the stability of the EER, EPR and PRP tripeptides docked to SARS-CoV-2 main protease, MPro (6M03) and epidermal growth factor receptor tyrosine kinase (4HJO) within 100 ns time scale and ligand-receptor interactions were evaluated. The metrics root-mean-square deviation, root-mean-square fluctuation, intermolecular hydrogen bonding, and radius of gyration revealed that the EER, EPR, and PRP tripeptides form energetically stable complexes with the target proteins. The binding free energies were calculated by the combination of Molecular Mechanics/Generalized Born Surface Area (MM/GBSA) and Molecular Mechanics/Poisson-Boltzmann Surface Area (MM-PBSA) methods (MM/PB(GB)SA). Principal Component Analysis on MD data was performed to evaluate the energy and structural information of the tripeptide-protein complexes. Additionally, in-silico structure-based pharmacological predictions were made and the anticancer and antibacterial activities of the tripeptides were predicted.
Keywords: Molecular Docking; Molecular Dynamics; Tripeptides